The Effect of Tunneling Incentives, Thin Capitalization, Financial Distress, and Earnings Management on Tax Aggressiveness - Rin Rin Imaniah; Kurnia (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
This research examines the simultaneous and partial effects of tunneling incentives, thin capitalization, financial distress, and earnings management on tax aggressiveness in Indonesian manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2021. Purposive sampling was conducted on a sample population of 213 manufacturing companies to obtain 420 observations. Eviews 12 software was utilized for the panel data regression analysis. The analysis of this research reveals that tax aggressiveness is simultaneously influenced by tunneling incentives, thin capitalization, financial distress, and earnings management. Partially, thin capitalization, financial distress, and earnings management have a positive effect on tax aggressiveness, but tunneling incentives have no effect.